The interactome of CCT complex – A computational analysis. (October 2016) - Narayanan, Aswathy; Pullepu, Dileep; Kabir, M. Anaul
Graphical abstract: Highlights: The interactomes of CCT in S. cerevisiae and H. sapiens were analysed and compared. Enrichment analysis revealed the association of CCT complex to diseases and stress. WD-repeat proteins, deacetylases, kinases, cytoskeletal proteins and other enzymes were prominent. Enrichment with pathways associated with ribosome and ribosome biogenesis was revealed. The study suggests that a network of chaperone and chaperonin systems work in concert. Abstract: The eukaryotic chaperonin, CCT (Chaperonin Containing TCP1 or TriC-TCP-1 Ring Complex) has been subjected to physical and genetic analyses in S. cerevisiae which can be extrapolated to human CCT (hCCT), owing to its structural and functional similarities with yeast CCT (yCCT). Studies on hCCT and its interactome acquire an additional dimension, as it has been implicated in several disease conditions like neurodegeneration and cancer. We attempt to study its stress response role in general, which will be reflected in the aspects of human diseases and yeast physiology, through computational analysis of the interactome. Towards consolidating and analysing the interactome data, we prepared and compared the unique CCT-interacting protein lists for S. cerevisiae and H. sapiens, performed GO term classification and enrichment studies which provide information on the diversity in CCT interactome, in terms of protein classes in the data set. Enrichment with disease-associated proteins and pathways highlight the medical importance of CCT. Different analyses converge, suggesting the significance of WD-repeat proteins, protein kinases and cytoskeletal proteins in the interactome. The prevalence of proteasomal subunits and ribosomal proteins suggest a possible cross-talk between protein-synthesis, folding and degradation machinery. A network of chaperones and chaperonins that function in combination can also be envisaged from the CCT interactome-Hsp70 interactome analysis.